2020
DOI: 10.1002/tox.23042
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K protects against 7,12‐dimethylbenz(A)anthracene induced hepatotoxicity in Wistar rats

Abstract: Humans are daily exposed to 7,12‐dimethylbenz(a)anthracene (DMBA), a well known polycyclic aromatic hydrocarbons (PAH). This study investigated the role of dietary intake of Vitamin K (VK), a polyphenolic compound, with potential antioxidative properties, against DMBA‐induced hepatotoxicity. Sixty experimental animals (120‐150 g) were divided into six groups (A‐F): Control, DMBA (80 mg/kg bw) only, VK (0.00 g/10 kg) diet only, VK (7.5 g/10 kg) diet only, DMBA + VK (0.0 g/10 kg) diet and DMBA + VK (7.5 g/10 kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The AST enzyme activity values in the treatment group and DMBA group had values that were above the normal group values. This is due to the DMBA induction reported by Dosumu et al [25] can increase AST levels. Researchers [26] also reported that the AST enzyme will be more produced when breast tumor growth occurs.…”
Section: Groupmentioning
confidence: 86%
See 1 more Smart Citation
“…The AST enzyme activity values in the treatment group and DMBA group had values that were above the normal group values. This is due to the DMBA induction reported by Dosumu et al [25] can increase AST levels. Researchers [26] also reported that the AST enzyme will be more produced when breast tumor growth occurs.…”
Section: Groupmentioning
confidence: 86%
“…These metabolites can then move to the mammary glands and form DNA adducts (DNA that binds to carcinogenic compounds). DMBA metabolism in the liver involves several stages involving phase I and II enzymes [25].…”
Section: Groupmentioning
confidence: 99%
“…Upregulation of iNOS expression produces NOs, which promote cancer formation and progression. 60,61 Rutin is a potent antioxidant polyphenol that reduces inducible nitric oxide synthase (iNOS) activity; attenuates mitochondrial damage; increases the glutathione (GSH)/GSSG ratio; enhances the activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx); and modulates the production of pro-inflammatory cytokines by decreasing TNF-α and IL-1β generation in microglia. 35 Src kinase is activated by nitric oxide generation, but this activation could be abolished with a nitric oxide scavenger.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress, resulting from the imbalance between the production of reactive oxygen species (ROS) and antioxidant activity, leads to macromolecular damage and subsequently chronic inflammation [48,49]. Both these features have deleterious effects on cell function, contributing to aging and the development of non-communicable chronic diseases, such as diabetes mellitus, hypertension, CVD, and CKD [4,50,51].…”
Section: Antioxidant and Anti-inflammatory Role Of Vitamin Kmentioning
confidence: 99%
“…Studies (both in vitro and in vivo) have shown that vitamin K decreases the levels of IL-2, IL-6, IL-17A, IFN-γ, nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2) expression through the inhibition of phosphor extracellular signal-regulated kinase (p-ERK) phosphorylation. This results in downregulation of NF-κB and p38 mitogen-activated protein kinase (MAPK) through the suppression of transcription factor AP-1, which leads to blocking of inflammatory pathways [50,57,60].…”
Section: Antioxidant and Anti-inflammatory Role Of Vitamin Kmentioning
confidence: 99%